Ivan Illich: An Intellectual Journey - Cayley, David (Ivan Illich: 21st-Century Perspectives, 2021)
Frontmatter -- Contents -- Introduction Ivan Illich as I Knew Him -- Prologue: Early Life -- 1. Exile -- 2. Cuernavaca -- 3. Church -- 4. Deschooling Society -- 5. Illich as Revolutionary -- 6. Disabling Professions -- 7. Certainties -- 8. Gender -- 9. Embodiment/Disembodiment -- 10. “A Bulldozer Lurks in Every Computer”: On Reading, Writing, and Language -- 11. To Hell with Life -- 12. Corruptio Optimi Pessima -- 13. Apocalypse -- 14. Illich’s Way of Life -- Epilogue The Art of Suffering -- Conclusion: An Intellectual Journey -- Notes -- Index